Richness and diversity of litter and soil fauna as affected by differences in three fir species - Çakır, Meriç (Bosque (Valdivia), 2018)
The main objective of this study was to evaluate the relationships between soil and litter properties and the distribution and diversity of microarthropods in Atatürk Arboretum (Turkey). Soil and litter samples were collected from three fir species: Taurus fir (TF – Abies cilicica Carr.), Uludağ fir (UF – Abies nordmanniana ssp. bornmuelleriana Mattf.) and Caucasian fir (CF – Abies nordmanniana ssp nordmanniana Mattf.). Microarthropods were sampled bimonthly using steel soil corers from May 2012 to March 2013. Redundancy analysis (RDA) detected clear relationships between microarthropods and litter mass and soil moisture. Litter mass at site CF was significantly larger than that at sites UF and TF. The mean annual density of microarthropods per square meter was 62,888 individuals.m-2 for site TF, 57,246 individuals.m-2 for site UF, and 59,959 individuals.m-2 for site CF. Shannon-Wiener diversity index (H′) values were significantly different among the study sites. Species diversity of soil arthropods was higher at site CF than at sites TF and UF. Results show that soil pH, litter mass and soil moisture are the principal attributes determining richness and diversity of microarthropods found under three different fir species.